Abstract book: 21st European Symposium on Suicide and Suicidal Behaviour - Grigienė, Dovilė; Skruibis, Paulius; Gailienė, Danutė (Vilnius University Proceedings, 2026)
The European Symposium on Suicide and Suicidal Behaviour is held every two years and brings together researchers, clinicians, and advocates from across Europe and beyond – sharing new ideas and research in suicide prevention. It remains one of the most significant events in the field. The 21st European Symposium on Suicide and Suicidal Behaviour (ESSSB21) is taking place on August 26–29, 2026, in Vilnius, Lithuania. The symposium is called ’Rethinking Suicide Research and Prevention’, as the event’s theme aims to encompass various disciplines, including not only psychology, psychiatry and public health, but also sociology, philosophy, policy studies and anthropology.